2013
DOI: 10.1111/his.12235
|View full text |Cite
|
Sign up to set email alerts
|

The density and type of MECA‐79‐positive high endothelial venules correlate with lymphocytic infiltration and tumour regression in primary cutaneous melanoma

Abstract: Our results support a predominant role for C-HEV in the recruitment of lymphocytes in cutaneous melanomas, mediated by CCL19 and CCL21, whereas the density of F-HEV strongly correlates with tumour regression, Therefore, cuboidal and flat HEVs may serve as indicators of the active and late quiescent phases, respectively, of tumour regression in cutaneous malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…Accordingly, HEVs with a thick wall and a small lumen -resembling the lymphocyte trafficking functional phenotype -were mostly located in areas with more prominent lymphocytic infiltration. These findings are consistent with previous results, where HEVs lined by a cuboidal endothelium were surrounded by more lymphocytes than those lined by a flat endothelium (39). In our patient cohort, HEVs with different morphologies were found in the same tumours.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, HEVs with a thick wall and a small lumen -resembling the lymphocyte trafficking functional phenotype -were mostly located in areas with more prominent lymphocytic infiltration. These findings are consistent with previous results, where HEVs lined by a cuboidal endothelium were surrounded by more lymphocytes than those lined by a flat endothelium (39). In our patient cohort, HEVs with different morphologies were found in the same tumours.…”
Section: Discussionsupporting
confidence: 93%
“…TLS are of increasing interest in tumor immunology because they are often associated with anti-tumor T cell responses and favorable prognosis of cancer patients. 53 Although high endothelial venules (HEVs) have been described in primary melanoma and have been linked to good clinical outcome, 54 , 55 conflicting results exist in regard to the presence of TLSs in primary melanoma, in spite of the fact that the latter frequently contain HEVs. 56 , 57 While we found a positive association between lymphatics and CD19 + cells in metastatic LNs, we did not detect many B cell clusters in the tumor samples examined here.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous recent studies have reported that PNAd and/or CCL21 are expressed in a variety of human tumors, including melanoma, breast, lung, ovarian, colorectal and testicular cancers (Cipponi et al, 2012; Coppola et al, 2011; de Chaisemartin et al, 2011; Martinet et al, 2012, 2011; Messina et al, 2012; Sakai et al, 2014). Several of these studies also showed that PNAd + HEV-like vasculature is associated with a positive prognosis (Avram et al, 2013; Martinet et al, 2012, 2011). These results suggest that inducing the development of HEV-like vasculature presents an alternative therapeutic path for enhancing intratumoral T-cell representation by enabling naïve T-cell entry into tumors, where they may become anti-tumor effectors.…”
Section: Tumors Develop Hev-like Vasculaturementioning
confidence: 93%
“…Primary human melanomas do contain HEV-like vessels expressing PNAd and CCL21 (Avram et al, 2013; Cipponi et al, 2012; Martinet et al, 2012). However, TLS are either entirely absent or present in only a small fraction of primary tumors (Cipponi et al, 2012; Ladányi et al, 2014).…”
Section: Tumors Develop Hev-like Vasculaturementioning
confidence: 99%